A Study to Analyze Teenagers’ Perception’s of, and Practices Regarding Branded Clothing - Hussain, Ghazal; Haq , Parveen (Nurture, 2017)
Wearing clothes with prestigious brand name is a very significant factor in every adolescent’s life. Teenagers today, are keener than ever to be accepted. Girls’ brand sensitivity is at its peak in their adolescent years. Branded clothing provides them an adequate platform to fulfil all their needs and desires. This study evaluates the female teenage perception of “Brands” and the factors that hinge their buying decisions in Pakistan. It tries to better understand the interest of teenager’s in brand names, their perceptions, shopping frequency, expenditure, information sources, purchase motivation, store selection criteria and their religious beliefs about the wearable. The study consists of descriptive research with a sample of 311 female teenage consumers A questionnaire was designed and self-administered to collect the data. Peers represent the most important predicator in their consumer’s socializing. As the age proceeds the shopping frequency raises. Certain criteria such as quality, price, sizes availability and store display carried more weight when making a store selection. Celebrities are found to be a reason behind the purchase. Brand loyalties among the respondents were seem to be very low. Educational and marketing implications are recommended. By analysing these factors a brand can be made more precision and profitable.